ANTIPROLIFERATIVE ACTIVITY OF RECOMBINANT HUMAN INTERFERON ALPHA2B ON ESTROGEN POSITIVE HUMAN BREAST CANCER MCF-7 CELL LINE - Ratih Asmana Ningrum; Popi Hadi Wisnuwardhani; Adi Santoso; Neng Herawati (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2015)
Indonesia is the top three countries with hepatitis and moreover has 40.000 cancer mortalities per year. Interferon alpha 2b (IFNα-2b) is a therapeutic standard for cancer and hepatitis B/C treatments. We developed recombinant human interferon alpha 2b (rhIFNα-2b) in methilotropic yeast Pichia pastoris X-33. The protein was produced as extracellular protein with 24 kDa in size. This research was aimed to characterize the protein based on its amino acid sequence and to study its antiproliferative activity on MCF-7 cell line. Amino acid sequencing by using MALDI TOF TOF mass spectrometry with trypsin as proteolytic enzyme identified protein as hIFNα-2b with 33% of amino acid coverage. The antiproliferative activity was determined by 3-[4.5-dimethyltiazol-2il]-2.5-diphenylltetrazolium bromide (MTT) assay. Based on several studies about the synergistic activity of rhIFNα-2b with other anticancer drugs, we combined our rhIFNα-2b with tamoxifen (tmx). The growth percentage of the cells after being treated with 1µM of tmx at various concentrations of rhIFNα-2b was compared with that of untreated cell. This study showed that the antiproliferative activity was dose-dependently. Cell viability assay with calcein and ethidium bromide-based staining by fluorescence microscope confirmed that the rhIFNα-2b had ability to inhibit proliferation of human breast cancer cell line MCF-7. Keywords: human interferon alpha 2b, Pichia pastoris, antiproliferative and MCF-7